Peranan Orang Tua terhadap Pendidikan Karakter Remaja Putri menurut Islam - Rahim, Arhjayati (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2013)
This paperdiscusses about the role of parents on character-building education of girl teenagers in Islam view. Teenager phase in their live is only coming once in a life, the beautiful phase and at once crucial because this phase is transitional phase physically, emotionally and physiology to arrive to another phase which is referred to adultness, to properness thought and action. This phase is also identical with socialization and adaptation with the surrounding, so it is not amazing when we find that the point of view and the attitude of teenagers in every country is different because it is related to the culture and social domination of the surrounding. Teenagers tend to come to vulnerable condition;therefore,they need control and guidance from their parents primarily to theirages-phases, the condition of their parents’ idea and their understanding about personality, along with religious thought which are aimed to build their girls’ character. Then, the girls can face their teenager-phase properly and accordance with Islam teachings. Finally, these girls’ character will make them smarter, skilful, and faithful to their religion, namely Islam.